A fatal case by a suicide kit containing sodium nitrite ordered on the internet - Durão, C; Pedrosa, F; Dinis-Oliveira, RJ (My University, 2020)
Fatal sodium nitrite poisonings are rare in the forensic context. The present work describes a first fatal case of sodium nitrite contained in a suicide kit that the victim acquired over the internet. The results of the autopsy showed general signs of asphyxia, such as intense cyanosis of the extremities, brown-gray-blue-red livor mortis, and some Tardieu petechiae in addition to intense visceral congestion. It is clear that forensic experts must be aware of the proliferation of this market and the risks of improper selling of these substances through suicide support networks available on the internet. The lack of knowledge of this reality may become unidentifiable, when toxicological analysis contemplates only the most classical and frequent substances involved in poisoning and reinforce the importance of a careful analysis of the death scene.
Keywords: Suícidio; Nitrito de Sódio; Medicina Legal; Suicide; Sodium Nitrite; Forensic Medicine